Euthanasia: Are we ready for it, or is it too late? - Pant, Basant (Nepal Journal of Neuroscience, 2022)
Euthanasia, also known as assisted suicide, is the act of intentionally ending the life of a person suffering from a terminal illness or incurable condition. The word "euthanasia" comes from the Greek words "eu," meaning "good," and "thanatos," meaning "death."1 Passive euthanasia entails the withholding treatment necessary for the continuance of life. Active euthanasia entails the use of lethal substances or forces (such as administering a lethal injection), and is more controversial. Euthanasia is a highly sensitive issue under scrutiny from medical, ethical, religious, cultural and socio-economic viewpoints.